The Dutch East Indies Government’s Program for Malaria Control Among the Population of Semarang, 1910–1940 - Muhammad Farid Husna; Ufi Saraswati (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
This research examines the Dutch East Indies government’s programs for addressing malaria among the population of Semarang City from 1910 to 1940. The purpose and objectives of this research are to identify and provide an overview of the programs implemented by the Dutch East Indies government to combat malaria, including the background of the malaria outbreak, its causes, and the government’s treatment strategies. The research method employed is qualitative research using a case study approach focused on the malaria endemic in the community of Semarang City from 1910 to 1940. This article was prepared using sources from government reports as well as several newspapers obtained from the Delpher platform, which is accessible online. Additional sources, such as books, were sourced from the Central Java Provincial Library and the Semarang City Archives and Library Service, which can be accessed directly on-site. The results of this research indicate that the Dutch East Indies government implemented several programs, such as collecting data on malaria victims, administering quinine, and improving village infrastructure to address the malaria epidemic in the community of Semarang City from 1910 to 1940.